A dynamically loaded ex vivo model to study neocartilage and integration in human cartilage repair - Trengove, Anna; Caballero Aguilar, Lilith M.; Di Bella, Claudia; Onofrillo, Carmine; Duchi, Serena; O’Connor, Andrea J. (Frontiers in Cell and Developmental Biology, 2024)
Articular cartilage injuries in the knee can lead to post-traumatic osteoarthritis if untreated, causing debilitating problems later in life. Standard surgical treatments fail to ensure long lasting repair of damaged cartilage, often resulting in fibrotic tissue. While there is a vast amount of research into cartilage regeneration, integrating engineered implants with cartilage remains a challenge. As cartilage is a load bearing tissue, it is imperative to evaluate tissue repair strategies and their ability to integrate under mechanical loading. This work established a dynamically loaded ex vivo model of cartilage repair using human cartilage explants. The model was used to assess the efficacy of a stem cell therapy delivered in a bioadhesive hydrogel comprised of photocrosslinkable gelatin methacryloyl (GelMA) and microbial transglutaminase to repair the model defect. Extensive neocartilage production and integration were observed via histology and immunohistochemistry after 28 days chondrogenic culture. Analysis of culture media allowed monitoring of glycosaminoglycan and type II collagen production over time. A mechanical assessment of integration via a push out test showed a 15-fold increase in push out strength over the culture duration. The model was successful in exhibiting robust chondrogenesis with transglutaminase or without, and under both culture conditions. The work also highlights several limitations of ex vivo models and challenges of working with bioreactors that must be overcome to increase their utility. This ex vivo model has the potential to delay the need for costly preclinical studies and provide a more nuanced assessment of cartilage repair strategies than is possible in vivo.